Conetronics in 2D metal-organic frameworks: double/half Dirac cones and quantum anomalous Hall effect. (9th November 2016) - Wu, Menghao; Wang, Zhijun; Liu, Junwei; Li, Wenbin; Fu, Huahua; Sun, Lei; Liu, Xin; Pan, Minghu; Weng, Hongming; Dincă, Mircea; Fu, Liang; Li, Ju
Abstract: Bandstructure with Dirac cones gives rise to massless Dirac fermions with rich physics, and here we predict rich cone properties in M 3 C12 S12 and M 3 C12 O12, where M = Zn, Cd, Hg, Be, or Mg based on recently synthesized Ni3 C12 S12 —class 2D metal-organic frameworks (MOFs). For M 3 C12 S12, their band structures exhibit double Dirac cones with different Fermi velocities that are n (electron) and p (hole) type, respectively, which are switchable by few-percent strain. The crossing of two cones are symmetry-protected to be non-hybridizing, leading to two independent channels at the samek -point akin to spin-channels in spintronics, rendering 'conetronics' device possible. For M 3 C12 O12, together with conjugated metal-tricatecholate polymers M 3 (HHTP)2, the spin-polarized slow Dirac cone center is pinned precisely at the Fermi level, making the systems conducting in only one spin/cone channel. Quantum anomalous Hall effect can arise in MOFs with non-negligible spin–orbit coupling like Cu3 C12 O12 . Compounds of M 3 C12 S12 and M 3 C12 O12 with different M, can be used to build spin/cone-selecting heterostructure devices tunable by strain or electrostatic gating, suggesting their potential applications in spintroincs/conetronics.